2020
DOI: 10.3390/ijerph17218066
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Development of an Expert System of Computerized Clinical Guidelines for COVID-19 Diagnosis and Management in Saudi Arabia

Abstract: The increasing number of COVID-19 patients has increased health care professionals’ workloads, making the management of dynamic patient information in a timely and comprehensive manner difficult and sometimes impossible. Compounding this problem is a lack of health care professionals and trained medical staff to handle the increased number of patients. Although Saudi Arabia has recently improved the quality of its health services, there is still no suitable intelligent system that can help health practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…The successful use of AI in healthcare in KSA depend on the awareness of medical experts of its applications. A recent study showed a deficit in the knowledge of the uses of AI and its implications on the job market among doctors, nurses, and technicians at four of the largest hospitals in Riyadh, Saudi Arabia [50]. On the other hand, recent questionnaire assessing attitudes of radiologists, radiology technologists, technicians, and radiological sciences students from different regions around Saudi Arabia on the use of AI in diagnostic radiology showed an acceptable level of knowledge on AI and a consensus to include AI education in medical curriculums four.…”
Section: The Saudi Experiencementioning
confidence: 99%
“…The successful use of AI in healthcare in KSA depend on the awareness of medical experts of its applications. A recent study showed a deficit in the knowledge of the uses of AI and its implications on the job market among doctors, nurses, and technicians at four of the largest hospitals in Riyadh, Saudi Arabia [50]. On the other hand, recent questionnaire assessing attitudes of radiologists, radiology technologists, technicians, and radiological sciences students from different regions around Saudi Arabia on the use of AI in diagnostic radiology showed an acceptable level of knowledge on AI and a consensus to include AI education in medical curriculums four.…”
Section: The Saudi Experiencementioning
confidence: 99%
“…This paper created and presented a novel knowledgebased strategy for supporting patients in the diagnosis of symptoms of the COVID-19 coronavirus, such as fever, cough, shortness of breath, or di culty breathing. drowsiness, discomfort, runny nose, and painful throat The Saudi MOH [14] states that suspected COVID-19 patients are either con rmed cases (asymptomatic and symptomatic) or negative examples (see Supplementary Materials S1 for a COVID-19 case de nition).To make the diagnosis, one must consider the existence of clinical symptoms, epidemiological considerations Chest imaging tests based on clinical imaging, laboratory ndings (nucleic acid ampli cation tests), and contact during incubation. The clinical classi cation encompasses cases involving expectant moms, elderly people, children, and newborns, as well as mild, moderate, severe, and critical cases (see Supplementary Materials S2 for clinical classi cation of con rmed cases).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several approaches have used rule-based analysis for detection of COVID-19. Banjar et al [36] developed an expert system that uses computerized clinical guidelines as rules for COVID-19 diagnosis and management. Salman and Abu-Naser [37] developed a rule-based system using the CLIPS and Delphi languages.…”
Section: Using Rules For Covid-19 Detectionmentioning
confidence: 99%